2007
DOI: 10.1007/s11431-007-0045-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological synthesis of nanophase PbS by Desulfotomaculum sp.

Abstract: The uniform nanoparticles PbS with diameters about 13 nm could be synthesized by Desulfotomaculum sp. under mild condition. The effects of the processing variables such as pH and temperature were investigated. The obtained products were in detailed by means of transmission electron microscopy (TEM) and X-ray diffraction (XRD), respectively. The results revealed that the PbS crystallites were identical in structure, shape and size under different temperatures while their morphology changed from rod to spheroida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…An alternative may be sought in biological methods of synthesis [4]. Microbial synthesis of metal [11,38] and semiconductor [41,12,9] nanoparticles has been widely reported, resulting from the microorganisms' intrinsic metalresistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative may be sought in biological methods of synthesis [4]. Microbial synthesis of metal [11,38] and semiconductor [41,12,9] nanoparticles has been widely reported, resulting from the microorganisms' intrinsic metalresistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to CdS NPs, other S-NPs, such as those of zinc sulfide (ZnS) and lead sulfide (PbS), have also been synthesized using SRB [100,[137][138][139]. For instance, Labrenz et al reported sphalerite ZnS NP formation within biofilms of Desulfobacteriaceae sp.…”
Section: Using Bacteriamentioning
confidence: 99%
“…Engels et al (2000) and Rudzinski et al (2004) reported that methanethiol under aerobic conditions is converted rapidly to dimethyldisulfide (DMDS) and/or dimethyl-trisulfide which caused precipitation for PbS nanoparticles. Gong et al (2007) obtained PbS nanoparticles by Desulfotomaculum sp. (strictly anaerobic sulfate-reducing bacteria).…”
Section: +mentioning
confidence: 99%